GABAC receptors in the lateral amygdala: a possible novel target for the treatment of fear and anxiety disorders? - Cunha, Catarina; Monfils, Marie H.; LeDoux, Joseph (Frontiers in Behavioral Neuroscience, 2010)
Activation of GABAARs in the lateral nucleus of the amygdala (LA), a key site of plasticity underlying fear learning, impairs fear learning. The role of GABACRs in the LA and other brain areas is poorly understood. GABACRs could be an important novel target for pharmacological treatments of anxiety-related disorders since, unlike GABAARs, GABACRs do not desensitize. To detect functional GABACRs in the LA we performed whole cell patch clamp recordings in vitro. We found that GABAARs and GABABRs blockade lead to reduction of evoked inhibition and increment of excitation, but activation of GABACRs caused elevations of evoked excitation, while blocking GABACRs reduced evoked excitation. Based on this evidence we tested whether GABACRs in LA contribute to fear learning in vivo. It is established that activation of GABAARs leads to blockage of fear learning. Application of GABAC drugs had a very different effect; fear learning was enhanced by activating and attenuated by blocking GABACRs in the LA. Our results suggest that GABAC and GABAARs play opposing roles in modulation of associative plasticity in LA neurons of rats. This novel role of GABACRs furthers our understanding of GABA receptors in fear memory acquisition and storage and suggests a possible novel target for the treatment of fear and anxiety disorders.